SOSIALISASI PHBS BERBASIS ANAK SEBAGAI AGEN PERUBAHAN DI DESA MEKARJATI - Faat Nasyiruddin; Pipit Amaliyah; Ussi Yuliana; Nurmalasari; Tri Wijayanti; Ahmad Yusuf; Diah Khosyatillah; Fais Firdaus; Johadhid Akmal Arif; Caskani (LPPM STAI Muhammadiyah Probolinggo, 2026)
Clean and Healthy Living Behavior (PHBS) serves as a vital foundation for public health. In practice, rural community awareness of PHBS, particularly in waste management and sorting, remains low. This community service activity positions school-age children as change agents who actively disseminate PHBS values to their families and communities. Implementation included direct socialization at six activity points, interactive lectures, blackboard instruction, and hands-on educational games using real waste materials to distinguish organic from inorganic waste. The program reached 248 participants from SDN Cipedang Bunder Grades 5 and 3, SDN Babakan Jati, Yayasan Islam An-Nur, Yayasan Dharma Satya Graha, and the Mekarjati Village Hall as the culminating event. Evaluations revealed significant knowledge improvement: participants correctly identifying the PHBS acronym rose from 13.7% to 92.7%. Through a domino effect, the program potentially reaches over 990 adults indirectly. These findings confirm that child-based PHBS education is an effective and efficient long-term social investment.